2021
DOI: 10.1186/s13052-021-01061-0
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient balance and micronutrient amounts through growth and development

Abstract: Nutrition is essential for human growth, particularly in newborns and children. An optimal growth needs a correct diet, in order to ensure an adequate intake of macronutrients and micronutrients. Macronutrients are the compounds that humans consume in largest quantities, mainly classified in carbohydrates, proteins and fats. Micronutrients are instead introduced in small quantities, but they are required for an adequate growth in the pediatric age, especially zinc, iron, vitamin D and folic acid. In this manus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(133 citation statements)
references
References 92 publications
1
121
0
11
Order By: Relevance
“…Human milk (HM) is typically the sole food source for the infants in the first 6 months of life, through which they acquire all elements necessary for their growth and development [1,2]. HM provides a constant supply of micro-and macronutrients, bioactive molecules including carbohydrates (lactose and glucose) and hormones (insulin) to the infant during early life, ensuring appropriate nutrition, maturation, and protection against infection and growth [3][4][5]. These components may also affect infant gut microbiota, appetite regulation and metabolism, as well as infant body composition (BC).…”
Section: Introductionmentioning
confidence: 99%
“…Human milk (HM) is typically the sole food source for the infants in the first 6 months of life, through which they acquire all elements necessary for their growth and development [1,2]. HM provides a constant supply of micro-and macronutrients, bioactive molecules including carbohydrates (lactose and glucose) and hormones (insulin) to the infant during early life, ensuring appropriate nutrition, maturation, and protection against infection and growth [3][4][5]. These components may also affect infant gut microbiota, appetite regulation and metabolism, as well as infant body composition (BC).…”
Section: Introductionmentioning
confidence: 99%
“…They found that lipid intake in the first 24 months was not associated in any way with overweight and obesity in later ages, and this data was further confirmed by Rolland et al, who even found a negative correlation between the hyperlipidic diet of a toddler and sera leptin levels at 20 years, the main anorexigenic hormone capable of being produced by the adipose tissue and the fat mass [45]. For these reasons, a diet with a total lipid amount exceeding the recommended 35-40% of the total energy daily intake during the first months of life could even be protective against the development of overweight and obesity in childhood and adolescence [33].…”
Section: Growth Obesity and Protein Leverage Hypothesismentioning
confidence: 99%
“…Moreover, reduced fat (skimmed) milk even doubles the protein contained in whole cow's milk [32]. Even most of the formula milks, based on cow's milk, contain a higher amount of protein than human milk, although much less if compared to commercial cow's ones [33].…”
Section: Growth Obesity and Protein Leverage Hypothesismentioning
confidence: 99%
“…The indirect calorimetry represents the gold standard for the determination of REE, but it is not always available in the hospital setting [ 37 ]. Therefore, in order to get an estimate of the amount of energy required by the body to maintain physiological functions, predictive equations are needed in order to determine the REE in children, such as the Schoefield formula [ 38 ].…”
Section: Nutritional Aspects: Critical Issues and Possible Solutionsmentioning
confidence: 99%